Acute Toxicity and Genotoxic Activity of Leunca (Solanum nigrum L.) Herb Ethanolic Extract - Rumiyati Rumiyati; Laili Nailul Muna; Devi Nisa Hidayati; Riris Istighfari Jenie (Indonesian Society for Cancer Chemoprevention, 2015)
Previous studies showed that Leunca herb ethanolic extract (LHE) has cytotoxic activity in several cancer cell lines such as HepG2 and HT-29. The extract also demonstrated as potential agent to be developed as co-chemotherapeutic in combination with doxorubicin and cisplatin. The combination is supposed to reduce occurance of cell resistance and toxicity towards normal cell. In order to verify safety before being applied to human, toxicological and genotoxic evaluation of the extract is important to be done. This research was therefore aimed to investigate acute toxicity and genotoxic activity of LHE. The acute toxicity study was carried out in three groups of 5 mice that was orally administrated by LHE at different doses consisting 300, 2000 and 5000 mg/kgBW. Mortality and sign of toxicity were observed during 7 days. Genotoxic activity was carried out using Mononuclear Polychromatic Erythrosite (MNPCE) assay at a doses range of 250, 500, and 1000 mg/kgBW. Cyclophosphamide (CYP) at the dose of 50 mg/kg was used as positive control. The result showed that LHE did not cause lethal effect on animal model up to doses of 5000 mg/kgBW. However, toxicity signs were found in animal model on day 0-6 of the observation. LHE had lower genotoxic activity compared to cyclophosphamide at the doses of 250, 500, and 1000 mg/kg. The low genotoxic activity and acute toxicity of LHE suggested that the extract might be safe to be used as medicine.Keywords: leunca herb ethanolic extract, genotoxicity, acute toxicity